2021
DOI: 10.1111/jfr3.12715
|View full text |Cite
|
Sign up to set email alerts
|

Flood hazard mapping of Sangu River basin in Bangladesh using multi‐criteria analysis of hydro‐geomorphological factors

Abstract: Flood havoc during 2019 in the Sangu River basin caused widespread damage to residents, crops, roads, and communications in parts of hills in Bangladesh. Developing flood hazard maps can play an essential step in risks management. For this purpose, this study assessed 12 hydro‐geomorphological factors, namely, topographic wetness index, elevation, slope, extreme rainfall, land‐use and land‐cover, soil type, lithology, curvature, drainage density, aspect, height above the nearest drainage, and distance from str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 54 publications
(63 reference statements)
0
31
0
1
Order By: Relevance
“…Analytical Hierarchy Process (AHP) is a popular multi-criteria decision technique that is widely used in different fields of studies. AHP technique was intensively applied in water resource development, allocation of water resources ( Hamdani, 2020 ; Zzaman et al., 2021 ; Sisay et al., 2021 ), flood susceptibility analysis ( Rincón et al., 2018 ; Swain et al., 2020 ), groundwater exploration ( Dar et al., 2020 ; Berhanu and Hatiye, 2020 ; Arulbalaji et al., 2019 ), water supply distribution systems, and selection of suitable dumping sites ( Ayaim et al., 2019 ; Chabuk et al., 2019 ; Şener et al., 2011 ; Sk et al., 2020 ). AHP technique has a capability of capturing the non-linear relationships among the key factors of suitable dumping sites selection criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Analytical Hierarchy Process (AHP) is a popular multi-criteria decision technique that is widely used in different fields of studies. AHP technique was intensively applied in water resource development, allocation of water resources ( Hamdani, 2020 ; Zzaman et al., 2021 ; Sisay et al., 2021 ), flood susceptibility analysis ( Rincón et al., 2018 ; Swain et al., 2020 ), groundwater exploration ( Dar et al., 2020 ; Berhanu and Hatiye, 2020 ; Arulbalaji et al., 2019 ), water supply distribution systems, and selection of suitable dumping sites ( Ayaim et al., 2019 ; Chabuk et al., 2019 ; Şener et al., 2011 ; Sk et al., 2020 ). AHP technique has a capability of capturing the non-linear relationships among the key factors of suitable dumping sites selection criteria.…”
Section: Methodsmentioning
confidence: 99%
“…These flooded locations were selected for training and validation of flood-prone areas. A training data set of 91 points -70% of the flooded siteswas randomly selected to produce a flood vulnerability map, and a validation data set of 39 points -30% of the flooded areaswas employed for result validation (Zzaman et al, 2021). In order to facilitate the validation, the area under the curve of the receiver operating characteristic curve (AUC-ROC) technique was used.…”
Section: Flood Inventory Mapmentioning
confidence: 99%
“…Slope is another topographical factor that affects flood modelling and occurrence since it affects the speed of surface water runoff (Tehrany et al, 2019;Islam et al, 2021). The steeper the slope the less vulnerable it is to flood events; steeper slopes show a lower infiltration rate and higher speed of flow (Das, 2020;Zzaman et al, 2021) . Thus, flat and gently sloping areas have a higher probability of flooding because of accumulation of water runoff (Tabarestani and Afzalimehr, 2021).…”
Section: • Slopementioning
confidence: 99%
See 1 more Smart Citation
“…In their study, Lee et al (2012) showed that different units of geology have various susceptibilities to flooding. Lithology greatly influences the hydrological and hydrogeological conditions by controlling the infiltration and surface runoff (Bui et al, 2019) as well as the slope of channel in temporal floods (Waqas et al, 2021;Zzaman et al, 2021).…”
Section: Lithologymentioning
confidence: 99%